니켈기 초내열합금의 감마프라임상의 성장거동 - 오준협; Junhyeob Oh; 조대영; Daeyoung Jo; 김홍규; Hongkyu Kim; 윤존도; Jondo Yun (대한금속·재료학회지, 56(1), 2018)
The mechanical properties of nickel-base superalloys used in disk and blade materials for gas turbine engines can be maximized by controlling their microstructure, such as the size of precipitates. In this study, we investigated the size of gamma prime precipitates after age hardening heat treatment at 650-980 ℃ for 1-48 hours. As the aging temperature and time increased, the grain size of gamma prime increased. The growth constants were 0.11, 0.24, 15.5 and 167 nm3/sec at 650, 760, 870, and 980 ℃ respectively. Activation energy for the growth of the gamma prime precipitates was determined to be 261±54 kJ/mol and reference studies have confirmed that Ni, Al, or Ti lattice diffusion in Ni or Ni3Al dominates the rate. The hardness increased with the decreasing size of gamma prime precipitates, and reached maximum at 24 nm, and decreased thereafter. The data on hardness vs. precipitate size followed the Hall-Petch relation over a precipitate size range from 24 nm to hundreds of nanometers. The maximum hardness at each annealing time increased with a reduction in the annealing temperature time. The optimum condition was determined to be 727 ℃ and 24 hours by using an approximation curve. The maximum hardness (520HV) was experimentally confirmed under this condition. The reduction in hardness with decreasing size might be due to changes in the misfit strain at the interface, decrease in the gamma prime volume fraction, or an increase in particle cutting events by dislocation. (Received August 4, 2017; Accepted September 29, 2017)